Novel Use of Low-Dose Radiotherapy to Modulate the Tumor Microenvironment of Liver Metastases - He, Kewen; Barsoumian, Hampartsoum B.; Bertolet, Genevieve; Verma, Vivek; Leuschner, Carola; Koay, Eugene J.; Ludmir, Ethan B.; Hsu, Ethan; Pisipati, Esha; Voss, Tiffany A.; Puebla-Osorio, Nahum; Cortez, Maria Angelica; et al. (Frontiers in Immunology, 2021)
Despite multiple therapeutic approaches, the presence of liver metastases carries a guarded prognosis, urgently necessitating further clinical and scientific research to develop curative interventions. The liver is an immunoprivileged organ that suppresses the effectiveness of immunotherapies in patients with hepatic metastases. Cancer immunotherapies have been successfully bolstered by low-dose radiotherapy (LDRT), which is capable of reprogramming the tumor microenvironment (TME) from an immunosuppressive to an immunostimulatory one. Likewise, LDRT may be able to revoke the immune privilege enjoyed by the liver, permitting successful immunotherapies there. Here, we first review challenges that face the treatment of liver metastases. We next outline emerging preclinical and clinical evidence supporting enhanced systemic tumor control of LDRT in the context of cancer immunotherapy. Finally, we will discuss the rationale of combining liver-directed LDRT with immunostimulatory strategies to overcome immune resistance and achieve better clinical response. This notion is supported by a recent case study in which a patient who had progressed following T cell therapy experienced a complete response after LDRT to the liver.